How the other half ate : a history of working class meals at the turn of the century - Turner, Katherine Leonard (California studies in food and culture, 2014)
In the late nineteenth and early twentieth centuries, working-class Americans had eating habits that were distinctly shaped by jobs, families, neighborhoods, and the tools, utilities, and size of their kitchens-along with their cultural heritage. How the Other Half Ate is a deep exploration by historian and lecturer Katherine Turner that delivers an unprecedented and thoroughly researched study of the changing food landscape in American working-class families from industrialization through the 1950s. Relevant to readers across a range of disciplines-history, economics, sociology, urban studies,